Modification of cultural heritage elicits disgust : the role of cultural essence, identification and sacredness of cultural heritage - Lim, Jonathan Zi Kai (2018)
Cultural heritage serves as an identity marker and anchor for members in the culture to develop their identities. In this paper, we examined if modifications to cultural heritage representations threaten the individual’s identity, and subsequently elicit disgust. We tested if the relationship between modification and disgust would be mediated by the embodiment of cultural essence, and whether this mediated relationship would be moderated by identification with and sacredness of Singapore’s cultural heritage. To test these propositions, we randomly assigned 163 Singaporean Chinese undergraduates into one of the three experimental conditions. Across the conditions, participants were presented with descriptions of the dishes representative of Singapore’s cultural heritage. In the no-modification condition, the dishes were described in their traditional forms. In the non-essence modification condition, the non-essential characteristics of the dishes were substituted. In the essence modification condition, the non-essential characteristics and essential characteristics of the dishes were substituted. Following each description, participants rated each dish on its disgust, appeal, and the embodiment of Singapore’s cultural heritage essence. Next, participants completed the measures for identification with Singapore’s cultural heritage, and sacredness of Singapore’s cultural heritage. Findings generally supported our hypotheses, with the exception of the moderating role of sacredness of cultural heritage. Participants rated the food products from the essence modification condition to have lower cultural essence and more disgusting. Individuals who identified strongly with cultural heritage reacted more strongly to the modifications. Such findings are pertinent to our understanding of cultural identity and why modifications to cultural heritage representations elicits disgust.